Development of a new integrated energy system with compressed air and heat storage options - Karapekmez, Aras; Dincer, Ibrahim; Javani, Nader (ELSEVIER, 2020)
The present study investigates a biomass driven power plant integrated with compressed air and thermal energy storage subsystems. Compressed air energy storage system exploits the pressurized air at non-peak periods to be used in peak times when there is a need for extra energy. Thermal energy storage systems including phase change material, allow the solar subsystem to operate independently in order to produce hot air when solar irradiation is insufficient. The energy stored in the present system is then supplied to both the gasifier and combustion chamber in order to achieve a higher combustion efficiency. Three different phase change materials (PCMs) are investigated and their efficiencies are comparatively evaluated. Among the considered PCMs, LiNO3 is the most suitable material for the considered system with 82% energy efficiency and 84% exergy efficiency. The current study also aims at designing a renewable energy based power plant which operates continuously through using storage subsystems and is more environmental benign compared to fossil fuel based conventional systems. In this regard, wet wood (CH1.46O0.64N0.002) with 15% moisture content is selected as a fuel instead of fossil-based fuels in order to reduce the greenhouse gas emissions and eliminate the dep endency on fossil fuels. A comprehensive thermodynamic analysis is conducted to evaluate the entropy generations, exergy destructions, and energy and exergy efficiencies. The highest overall energy and exergy efficiencies are obtained as 28.58% and 24.08% in the discharging period, respectively.
Keywords: Biomass; Compressed air storage; Efficiency; Energy; Exergy; Phase change materials; Thermal energy storage; PILOT-SCALE DEMONSTRATION; THERMODYNAMIC ANALYSIS; TECHNOLOGIES; OPTIMIZATION; 1ST; Energy & Fuels